Prescribed performance tracking for a class of uncertain nonlinear systems with actuator failures. (25th May 2022) - Liu, Jiehan; Yi, Peng; Wang, Chaoli
Abstract: In this article, we consider the design of a tracking controller for a class of uncertain nonlinear systems with external disturbances and actuator failures and achieve predesignated performance results on the tracking error. First, since the existing prescribed performance strategies are unable to specify performance bounds in an arbitrary way, we propose a new tool to address the prescribed performance issue by constructing chained first‐order filters and an input switching method. With the aid of the new and flexible prescribed performance tool, any predesignated continuous bounds can be formed by setting the reference coordinate values, sufficiently small coordinate value intervals and the gain parameters of the filters. Second, a full state feedback controller design scheme based on the prescribed performance bounds, which describe the convergence rate and maximum overshoot of the tracking error, is proposed. It is proven that the tracking error always satisfies the prescribed performance bounds. Finally, simulation studies are used to illustrate the effectiveness of the proposed tool and the correctness of the established theoretical results.